2005
DOI: 10.1177/155005940503600303
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer's Disease: Models of Computation and Analysis of EEGs

Abstract: In a recent article the authors presented a comprehensive review of research performed on computational modeling of Alzheimer's disease (AD) and its markers with a focus on computer imaging, classification models, connectionist neural models, and biophysical neural models. The popularity of imaging techniques for detection and diagnosis of possible AD stems from the relative ease with which neurological markers can be converted to visual markers. However, due to the expense of specialized experts and equipment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
52
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(57 citation statements)
references
References 136 publications
(164 reference statements)
5
52
0
Order By: Relevance
“…In this sense, an enhanced activity in lower frequency bands has been previously observed along with the severity of AD [12,43,44], which is in agreement with the high correlation in the relative power of δ band.…”
Section: Insert Figure 1 About Heresupporting
confidence: 86%
See 1 more Smart Citation
“…In this sense, an enhanced activity in lower frequency bands has been previously observed along with the severity of AD [12,43,44], which is in agreement with the high correlation in the relative power of δ band.…”
Section: Insert Figure 1 About Heresupporting
confidence: 86%
“…Some abnormalities in moderate and severe AD patients' EEG and MEG background activity have been observed [11][12][13]. AD patients show a decrease of coherence values at the α and β bands in EEG [14,15], together with a slowing of spontaneous electrical brain activity.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, recent research has suggested the limitations of neuroimaging techniques in accurately detecting tangles and plaques [4]. The use of quantitative electroencephalogram (EEG), on the other hand, has shown to be a viable lesscostly alternative, with diagnostic accuracy inline with those obtained with more expensive neuroimaging techniques [5].…”
mentioning
confidence: 99%
“…With spectral analysis, the consensus is that EEG spectral power is reduced with AD in the alpha (8)(9)(10)(11)(12) and beta (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) Hz) frequency bands, and increased in the delta (0.1-4 Hz) and theta (4)(5)(6)(7)(8) bands. Spectral coherence (a measure of brain connectivity), in turn, has shown reduced values in AD when studying interhemispheric interactions, and has also been shown to be related to disease progression [6].…”
mentioning
confidence: 99%
“…The most distinctive of these effects include: i) noticeable shift occurring in the EEG power spectrum (e.g., slowing of the EEG) [8]- [10]; ii) reduced inter-hemispherical spectral coherence [11]- [13]; iii) decreased EEG "complexity," likely caused by the reduction in nonlinear connections between cortical regions or even neuronal death [7]; and more recently, iv) a change in neuromodulatory behaviour measured via EEG amplitude modulation analysis [5], [14]. Many of these changes have been shown to be related [15] and diagnostic accuracies in line with more advanced neuroimaging techniques (e.g., fMRI) have been achieved [16].…”
Section: Introductionmentioning
confidence: 99%